THE ROLE OF INDEPENDENT EDUCATION IN THE DEVELOPMENT OF ACADEMIC MOBILE STUDENTS - Qoraev Samaridin Barakaevich (Galaxy International Interdisciplinary Research Journal, 2022)
The article discusses the principles of improving the system of independent learning, the opportunities of students in the trajectory of independent learning and the problems that need to be addressed in the organization of independent learning.